Pembelajaran Ilmu Tajwid Melalui Media Audio Visual pada Anak-anak di Rumah Belajar Mahapeserta Didik KKN Desa Cempaka Mulia Barat - Siti Fathonatul Hikmah; Junita Wulandari; Muhammad Rifani Al-Ghazali; Hadma Yuliani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This service aims to find out the implementation of tajweed learning through audio-visual media by KKN students in Cempaka mulia Barat village in the learning house activity program. This service method uses descriptive qualitative with data collection techniques in the form of observation. Data analysis is done descriptively interpretative. The results of the service show that audio-visual media can be applied effectively to children in the village of cempaka mulia barat, because this method is able to increase children's interest in reading the Qur'an and reduce boredom in the teaching and learning process.